The Influence of Product Quality and Promotion on Purchase Decisions on Culinary MSME Consumers in Medan City - Dedy Lazuardi (Outline Publisher, 2026)
Purpose: This study investigated the influence of product quality and promotion on consumer purchasing decisions within the culinary micro, small, and medium enterprise sector in Medan City. Methods: Researchers employed a quantitative causality approach to collect primary data from consumers who had completed at least one transaction. Data collection involved a structured questionnaire instrument distributed to a purposively selected sample. Researchers systematically analyzed the data using a multiple linear regression analysis method to test the hypothesized effects. Results: Statistical analysis results proved that product quality positively and significantly influenced purchasing decisions with an estimated value of 0.452. Furthermore, promotion also exerted a positive and significant influence on purchasing decisions with an estimated value of 0.318. Simultaneously, product quality and promotion explained 62.4 percent of the total variation in consumer purchasing decisions. Conclusions: This research concluded that the combination of high product quality standards and aggressive promotional strategies successfully drove transaction decisions effectively. Originality/value: These findings emphasized the critical need for culinary business practitioners to consistently balance digital marketing visibility with the assurance of authentic product value to sustain business continuity amidst a highly competitive market.